Social Structure, Educational Attainment and Admission to Law School - Alex Ziegert (Legal Education Review)
[Extract] “From the moment you are born, ...”, a recent TV advertisement tells us, “... the odds are stacked against you!”. The advertisement then goes on to demonstrate how minimal the chances are to incur certain favourable life-events. It suggests that, rather than trying hard, it is better to play the lottery as a way of overcoming the adversities of everyday life. However doubtful the actuarial calculations may be which are used in the advertisement, it makes a forceful point: what we expect to be, and what — in a democratic society — is promised to be, apparent equality of opportunities turns out as a maze of barriers, dead-ends and capricious events. What the lottery advertisement implies, but what the liberalist democratic formula fails to tell us generally, is that the equal chances provided by the social life of any society are not only as bad as, but in fact worse, than chances provided by a lottery. Different from the lottery, the “odds” in real life are systematically “loaded when equal access is attempted to health, wealth, power and status, or to whatever seems worth achieving in a given society. What appears to be chance, or at best fate and providence, is evidently the invisible hand of social structure, tipping the scales consistently in the direction of how that structure itself operates at any given time in the life of an individual from the moment the individual is born. This observation is, of course, hardly original. However, it is important to keep it in mind when one wants to assess the practices of admitting access to tertiary education — a resource in all modem societies — and when one wants to design policies which are aimed at reforming the access to law schools — a formidable resource in all societies which follow the common law tradition. Viewed from the aspect of the complex and pervasive historically entrenched social structure and social processes, to change admission practices effectively is an awesome task. Admission policies which are advocated as “new” can be safely assumed to be merely the administration of more of the same unless enough leverage can be mobilised to unsettle the systematic bias of social structure and to neutralise some of the thoroughly debilitating effects of its invisible hand. Obviously, to attain such leverage is beyond the scope of individual universities and/or their law faculties, and it is outside the work practices which are employed in the admission of students. We must assume that whatever universities can or will do necessarily amounts to not much more than tinkering with the systematic bias of social structure. There is now compelling evidence that this is in fact the only result which universities have achieved in a fairly long history of admission policy reforms in the tertiary education sector in Australia. There is also increasing consensual knowledge that the even more comprehensive and better coordinated actions and programmes on state or national government level, which were designed to affect the social mix of undergraduates in Australia and overseas had no, or only a limited effect. Often, the small effect achieved by incisive single-measure government intervention or by broad equal opportunity policies is counteracted by subsequent changes in admission policies which in turn make access to higher education even more highly competitive. Any gains made by these policies are whittled away by the social forces at work on a deeper and more complex level of a given society. It is important to note, however, that this bleak picture changes somewhat where specific target groups are concerned. Here more narrowly tailored government programmes can be shown to be reasonably successful. Special programmes of this kind remain promising but are, by definition, limited in their outcomes. Finally, a third and different case in the history of admission practices in educational organisations in general and, especially, in the tertiary education sector, is the case of women. It provides us with the evidence that the dynamics of the invisible hand of social structure can be forced over time even if ever so slightly. Women, coming from a position of practical exclusion from higher education, have achieved, at least nominally, equal access to higher education with men, even if, as yet, actual admission practices are still quite patchy. As the following discussion will show, this more complex change in admission practices but, more importantly, in educational attitudes towards girls and women generally, has had and still has crucial consequences for structural change in a given society. This potential for change is related to the pivotal role women have in societies as mothers who are, rather than fathers, effectively in charge of the socialisation of their children. This is generally the case in all societies but plays a particularly important role in the educational programmes of societies which are on the way to become modern, industrial societies and possibly post-modem societies. It appears, then, that the educational attainment of mothers is one of the most powerful single predictor variables for structural change and for intergenerational transmission in societies. A review of admission policies has to address this observation.